Relations entre spectres polliniques contemporains et topographie dans la vallée de la Coppermine, Territoires du Nord-Ouest - Geurts, M.-A. (Canadian Journal of Botany, 1983)
Thirty six moss polster samples from forest tundra and shrub tundra collected along the Coppermine River Valley, N.W.T., result in six pollen assemblages associated with type landforms. Forest sites on moderately steep slopes of approximately 12° yield spectra dominated by spruce. Spectra dominated by Salix (>50%) exist only at isolated sites where the shrub is the principal species found. Flat, well-drained surfaces on gentle slopes exposed to wind produce spectra dominated by more than 50% Betula. The assemblage Betula–Ericales corresponds to gentle slopes actively modified by cryogenic processes. The assemblages Betula–Salix and Salix–Betula are found on gentle, poorly drained slopes or in zones of shrub tundra where Salix is a pioneer species on surfaces newly exposed to weathering. The assemblage Betula–Picea is not a specific indicator since it is found on various topographic sites. The paper proposes one example of the utilization of these relationships between pollen spectra and landforms, for the interpretation of fossil pollen samples. This example shows that the variations in pollen spectra of a stratigraphic diagram do not exclusively reflect climatic variations or ecologic successions, but may be due to environmental change brought about by geomorphologic processes.